Effect of electrophoretic deposition parameters on coating thickness and deposit yield of non-colloidal graphite particles - Lau, Kok Tee; Sorrell, Charles Chris (Penerbit UTM Press, 2024)
Electrophoretic Deposition (EPD) has become a method for fabricating and enhancing electrodes for electrochemical energy storage (EES) devices. This article explores the impact of dominant EPD parameters on the deposit yield and coating thickness of graphite produced from an organic-based graphite particle suspension. The deposit yield follows a linear Hamaker's law at voltages below 50 V, with a deposition time of up to 5 minutes and solid loading between 2.5 to 12.5 mg/mL. The study also demonstrates the successful deposition of negatively charged and non-colloidal sized graphite particles, which are previously dispersed in n-butylamine-acetone without the use of charging or binding additives. This later forms a coating with a relatively strong binding strength of graphite particles on the steel anode. EPD of graphite suspension with a concentration of 5 mg/mL at a deposition voltage of 10 V and 5 minutes deposition time is capable of producing a graphite coating thickness of 70 m. This research demonstrates the high-yield capability of EPD of organic-based graphite particles on metal anode and provides valuable insight for future investigations into application of binderless graphite suspension particles for electrode materials in energy storage systems.